The Twins of the Rain Forest - Ukoli, Neville M (Longman Nigeria Ltd, 1968)
This book is a new series of exciting stories which will be found especially enjoyable by students in the upper classes of primary schools.
Keywords: Juvenile literature-Fiction-Nigeria (English)